Occupational health services - Ramírez, Augusto V. (2012)
Medical surveillance via occupational medical examinations is the most widely tool used in prevention and control of job-related diseases. Its management by the occupational physician allows recognition of the occupational disease. By developing programs of preventive-promotional health and occupational examinations the Occupational Health Services make possible early recognition of labor health problems. Their goal is to prevent work-related diseases. Companies must establish and maintain labor health services integrated by specialized physicians in occupational medicine as head of a team that includes occupational nurses, industrial hygiene, and other technicians specialized in labor health-related fields.